Benzobis(imidazole) derivatives as STAT3 signal inhibitors with antitumor activity. (1st July 2022) - Liu, Yi-Chen; Yang, Ya-Dong; Liu, Wen-Qiang; Du, Ting-Ting; Wang, Ru; Ji, Ming; Yang, Bei-Bei; Li, Li; Chen, Xiao-Guang
Graphical abstract: Highlights: A series of benzobis(imidazole) derivatives were found to have inhibitory activity against the IL-6 induced JAK/STAT3 signalling pathway. The most promising compound 24 could inhibit tumor cell proliferation and migration by inhibiting STAT3 signalling pathway. Compound 24 could inhibit the phosphorylation of STAT3 in tumor cells, induce tumor cells apoptosis and cycle arrest. Compound 24 could inhibit tumor growth in HepG2 xenograft model. Abstract: Polycyclic aromatic systems have been considered good biological probes, but some may also be good scaffolds for drug development. In this study, a series of benzobis(imidazole) derivatives were identified as STAT3 signal inhibitors, among which compound 24 showed significant inhibition of IL-6 induced JAK/STAT3 signalling pathway activation. Moreover, 24 inhibited cancer cell growth and migration, and induced cell apoptosis as well as cycle arrest in human hepatocellular carcinoma cells (HepG2) and oesophageal carcinoma cells (EC109). Compound 24 also displayed obvious antitumor activity in a mouse HepG2 cell xenograft tumor model without affecting the body weight. These results confirmed that 24 was a potential STAT3 signal inhibitor with certain antitumor activity.